Start-up firms. Strategic or suck-it-and-see? - Anthoney, Julian (2012)

(untitled)
This document’s aim is to contribute to the existing research on strategic entrepreneurship by investigating whether start-up firms in the East Midlands consider strategy and planning or whether they simply launch following recognition of an opportunity.